An exploratory study on causes and effects of miscommunication error among maintenance crew - Munirah Mohd Fadzil,; Izamarlina Asshaari,; Muhammad Cairel Alban Shaharugi,; Abdul Ghani Abdul Samad,; Puteri Nur Syaza Wardiaha, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Verbal and written communication are both valid methods for conveying a message; communication is an extremely important factor in the process of passing on information. In both the aviation industry and the maintenance industry, poor communication is consistently a major issue. The failure of the members of the maintenance crew to communicate effectively could, without a doubt, place the lives of other people in jeopardy. Therefore, this study is conducted to investigates the factors that contributed to, and the consequences of, miscommunication error and the correlation between it. The cause depicted for miscommunication error among maintenance crew are poor language proficiency, poor documentation, lack of technical term proficiency and lack of communication meanwhile its negatively impacts maintenance organization. To identify the causes and consequences of miscommunication errors among maintenance crew, the survey data is analyzed using a bar chart, and Spearman correlation is used to investigate the relationship between causes and effects. According to the results of the Spearman correlation, there are five moderately strong correlations between causes and effects and three weak correlations. It is recommended that further research be done on engineers and technicians working in maintenance repair organizations (MRO) to gather more reliable data.